The vertical profile of nitrate in bakuok lake aursati Village tambang subdistrict kampar district Riau province - Nababan, Krismanto Viade; Siagian, Madju; Simarmata, Asmika Harnalin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research has been done from March to April 2014 in the Bakuok Lake,Aursati Village, Tambang Subdistrict, Kampar District, Riau Province. This research aimsto understand the vertical profil of nitrate in this lake. The research used survey method.The nitrate samples were collected from three station namely station I at inlet of lake,station II in the middle of lake and station III in the end of lake. There were three samplingsites in each station were in the surface, 1,5 Secchi depth and bottom. Sampling was donethree times, once a week. The result shown nitrate concentration in surface : 0,01-0,03mg/L, in 1,5 Secchi depth 0,03-0,06 mg/L and in the bottom 0,05-0,12 mg/L. The nitrateconcentration in surface lower than in the 1,5 Secchi depth and in the bottom and nitrateconcentration increase with the depth. Water quality result shown pH:6, DO: 1,78-5,33mg/L, CO2: 4,66-15,31 mg/L, depth: 208-332 cm, transparency: 74,3-93,7 cm andtemperature: 29,6-30oC. Based on data obtained, it can be concluded the consentration ofnitrate in Bakuok Lake showed the trophic status was Oligotrophic and water quality stillsupport the life of aquatic organisms.Keywords: nitrate, the vertical profile, Bakuok Lake